2017
DOI: 10.1021/acs.macromol.7b01283
|View full text |Cite
|
Sign up to set email alerts
|

Annealing-Induced Circular Dichroism Enhancement in Luminescent Conjugated Polymers with an Intramolecular Stack Structure

Abstract: Two poly­(diphenylacetylene) derivatives containing identical chiral pinanyl groups on the para- and meta-positions of the side phenyl ring were prepared, and their circular dichroism (CD) and photoluminescence (PL) spectra were compared. The magnitudes of circular polarization (g CD) of the para- and meta-polymers were determined to be 3.1 × 10–3 and 1.4 × 10–3, respectively. The PL quantum yield (PLQY) of the para-polymer was much greater (27.8%) than that of the meta-polymer (2.61%). When the two polymers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
(57 reference statements)
0
15
0
Order By: Relevance
“…On the other hand, in the case of asymmetric PDPAs, Kwak, Aoki and co-workers made great contributions to the study of their luminescent properties and to the achiral-to-chiral transformations of PDPAs. [78,82,[85][86][87][88][89] To perform these studies, a catalyst developed by Masuda [TaCl 5 -n-Bu 4 Sn] was used. [77] Also with asymmetric PDPAs, Tang and co-workers reported polymers prepared with the WCl 6 -Ph 4 Sn [83,84] catalyst that Maeda also employed for the preparation of optically active PDPAs with application as chiral stationary phases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in the case of asymmetric PDPAs, Kwak, Aoki and co-workers made great contributions to the study of their luminescent properties and to the achiral-to-chiral transformations of PDPAs. [78,82,[85][86][87][88][89] To perform these studies, a catalyst developed by Masuda [TaCl 5 -n-Bu 4 Sn] was used. [77] Also with asymmetric PDPAs, Tang and co-workers reported polymers prepared with the WCl 6 -Ph 4 Sn [83,84] catalyst that Maeda also employed for the preparation of optically active PDPAs with application as chiral stationary phases.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting family of helical polymers are the poly(diphenylacetylene)s (PDPAs) [71–93] that resemble PPAs in the main chain, which in both cases is made up of conjugated double bonds. However, the presence of a phenyl group on each carbon of the double bond in PDPAs makes the properties of both materials very different.…”
Section: Introductionmentioning
confidence: 99%
“…The optical activity induced in the PDPA was retained at ambient temperature but almost disappeared at high temperatures. Helically stacked aromatic groups with one particular handedness along the helical backbone twisted in one direction have been proposed for their optical activity during the polymerization or annealing process in chiral solvents. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, besides the four stereoregularities (Chart ), further complicated regioregularities (head-to-tail, head-to-head, and tail-to-tail) exist for asymmetrically substituted poly­(disubstituted acetylene)­s (Chart ), resulting in complicated NMR spectra. In addition, symmetrically substituted PDPAs are considered to be mostly insoluble in common organic solvents. ,, The appearance of CD signals in optically active PDPAs implies a chiral or helical structure that is induced in the PDPAs; however, it is not straightforward to unambiguously determine the helical structures (helical sense and helical sense excess). , Obviously, symmetrically substituted PDPAs have an advantage over asymmetrically substituted ones because of no regioregularity other than the configuration (cis or trans) of the main chains, thereby facilitating identification of the main-chain stereoregularity of PDPAs by spectroscopic means, which appears to be of primary importance for elucidating the structure of helical PDPAs.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal annealing is necessary, i.e., 4 h at 80 °C, to induce a preferred handedness in the PDPA main chain. [81,82,86,99] Recently, Maeda and co-workers studied the secondary structure of symmetric PDPAs bearing para-substituted carboxy pendant groups. [79,80] By using a combination of 1 H and 13 C NMR, IR, Raman, VCD and ECD spectroscopies, they found that this polymer adopts a preferred cis-transoidal structure, where P or M-helical senses can be induced by thermal annealing in water in the presence of chiral amines.…”
Section: Introductionmentioning
confidence: 99%